Designing Next Generation of Persistent Luminescence: Recent Advances in Uniform Persistent Luminescence Nanoparticles. Issue 14 (24th February 2022) - Huang, Kai; Le, Nhu; Wang, Justin S.; Huang, Ling; Zeng, Le; Xu, Wei‐Chu; Li, Zhanjun; Li, Yang; Han, Gang
Abstract: Persistent luminescence is a unique optical process where long‐lasting afterglow persists after the cessation of excitation. Nanoscale persistent luminescent materials are getting increased research interest from various fields due to their unique optical property. In recent years, inspiring achievements have been made to produce uniform persistent luminescence nanoparticles (PLNPs) in a controllable manner, unleashing their fascinating potential, surpassing other types of luminescent materials in a wide variety of application such as high‐contrast bioimaging and high‐resolution X‐ray detection. In this review, the evolution of uniform PLNPs, from their bulk phosphor counterparts, to the "top‐down" preparation of nanoscale persistent luminescent materials, to the recent "bottom‐up" synthesis of uniform PLNPs is first summarized. The respective milestones of uniform PLNPs prepared by templated synthesis, aqueous synthesis, and colloidal synthesis are highlighted. The key optical properties that can be enhanced in uniform PLNPs, including increasing the persistent luminescence intensity, tuning the excitation irradiance, as well as the emission wavelengths are then analyzed. Detailed strategies to enhance each optical property are also discussed in various sections. Finally, future challenges are highlighted with respect to the perspectives on the development of next‐generation PLNPs with novel applications. Abstract : Persistent luminescence nanoparticles (PLNPs) possess long‐lasting afterglow after the excitation ceases, demonstrating merits for various applications. The recent rapid progress of uniform PLNPs boosts their biomedical applications. This review highlights milestones of uniform PLNPs syntheses, analyzes key strategies for enhancing their optical properties, and envisions the challenges and potential future directions of uniform PLNPs for novel applications.